The elusive scale economies of the largest banks and their implications for global competitiveness - Joseph P. Hughes (Rutgers University, Department of Economics, 2011)
In the wake of the financial crisis that began in 2007, policy makers have focused again on the largest financial firms to consider the association of their size with systemic risk. An equally important question examines whether their size benefits the economy. In particular, is the size of our largest financial institutions the result of technological cost advantages that improve the efficiency of their capital allocation and liquidity and enhance their international competitiveness? Or is it the result, not of technological cost advantages, but of safety-net subsidies that confer too-big-to-fail cost advantages and foster moral hazard in investment decisions. This paper reviews the evidence of large scale economies that increase with size and considers the credibility of this evidence by examining details of how scale economies are measured and why evidence of scale economies eludes many investigations. A method of estimating scale economies developed by Hughes, Lang, Mester, and Moon (1996) distinguishes the underlying scale effects on cost from the effects on costs of size-related changes in risk-taking, which can obscure technological cost advantages, such as those due to better diversification. It reviews evidence that technology, not too-big-to-fail subsidies, accounts for the cost advantage of the largest financial institutions. Finally, it considers the implications of scale economies for scaling back the operations of the largest financial institutions and for the global competitiveness of smaller institutions.
Keywords: D20; D21; G21; 330